The Role of Accompanying Teachers in Improving Students’ Achievement on the Topic of Growth and Development at SMP Negeri 6 Banda Aceh - Khairunnisa; Saudah; Ibrahim; Muhammad Ridhwan; Evi Apriana (Postgraduate, University of Mataram, 2025)
This study aims to describe the role of accompanying teachers in improving students’ learning achievement on the topic of Growth and Development at SMP Negeri 6 Banda Aceh. The research employed a quantitative approach using a quasi-experimental method. The subjects consisted of 32 students of Grade VII-8 in the 2025/2026 academic year. Data were collected through learning achievement tests (pre-test and post-test), observation of learning activities, and interviews with the accompanying and biology teachers. Data analysis was conducted descriptively and inferentially using the Normalized Gain (N-Gain) formula to determine the improvement in students’ learning outcomes. The results showed a significant improvement in student achievement, with the average pre-test score of 60 increasing to 88–90 on the post-test. The presence of an accompanying teacher played an important role in creating an active and structured learning atmosphere, supporting students who experienced learning difficulties. Collaboration between the accompanying teacher and the biology teacher in planning, implementing, and evaluating the learning process proved effective in enhancing students’ conceptual understanding, motivation, and learning outcomes on the topic of growth and development. Therefore, it can be concluded that accompanying teachers play a strategic role in improving students’ learning achievement through academic, motivational, and collaborative assistance in the classroom. The application of this mentoring model can serve as an effective alternative to enhance the quality of science learning at the junior high school level.